2022
DOI: 10.3390/ijerph19138136
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Various Nutrient Ratios in Fodder Plants as an Effect of Compost and Fly Ash Application

Abstract: Despite the popularity of concentrated feed, fodder crops are still important, especially in organic livestock farming. However, this type of feed must meet certain criteria, which are often described using correct nutrient ratios. The research investigates the influence of compost and fly ash on quantitative changes in nutrient ratios determined for lupine and oat cultivated on soil slightly contaminated with Cu. A pot experiment was conducted on medium soil. Immobilizing agents (compost and fly ash) were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Usually the assessment of the effect of agricultural factors on the chemical compounds of plant biomass is conducted in one way throughout fertilization (Manas et al, 2018;Jakubus and Bakinowska, 2020b;Herencia et al, 2011). However, the reports may occasionally be found (Rady et al, 2016;Jakubus and Bakinowska, 2020a;Jakubus and Graczyk, 2022) related to the assessment of the effect of fertilization on the ratios between the nutrients. In cited studies it has been clarified and confirmed that fertilization influences the nutrient contents in plant biomass, as well as the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Usually the assessment of the effect of agricultural factors on the chemical compounds of plant biomass is conducted in one way throughout fertilization (Manas et al, 2018;Jakubus and Bakinowska, 2020b;Herencia et al, 2011). However, the reports may occasionally be found (Rady et al, 2016;Jakubus and Bakinowska, 2020a;Jakubus and Graczyk, 2022) related to the assessment of the effect of fertilization on the ratios between the nutrients. In cited studies it has been clarified and confirmed that fertilization influences the nutrient contents in plant biomass, as well as the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…This element is also required for muscle contraction and nerve impulse transmission (Cherian, 2019). Despite the considerable importance of nutrient ratios and the appropriate balance of nutrients in fodder plants referenced in the literature, as yet there is only fragmentary information concerning the assessment of the quality of various crops (vegetables, grassland, crops, herbaceous or leguminous plants) using the ratios of their nutrients (Jakubus and Bakinowska, 2020a;Jakubus and Graczyk, 2022). Moreover, in the literature there are very different and broad ranges of nutrient contents given as optimal and critical levels for crops (Mahler, 2004;Prasad, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations